Analysis and optimization of relevant parameters of blade coating and gravure printing processes for the fabrication of highly efficient organic solar cells - Schneider, Artur; Traut, N.; Hamburger, Manuel (Solar energy materials & solar cells, 2014)
Large area processing of organic semiconductors to photovoltaic cells and modules opens up a large potential for commercialization. At the same time, the scale-up of fabrication techniques entails evaluation and optimization of several process parameters. In this study, comprising a state-of-the-art absorber polymer (PTB7, together with PC60BM), we vary processing parameters for blade coated and gravure printed active layers and evaluate their effects on solar cell performance. Thus, efficiencies of up to 3.6% for coated and 1.6% for printed cells on a flexible substrate could be obtained.